Analisis Kualitas Produk, Harga dan Pengaruhnya Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Sepeda Motor Honda - Nasikhatun Hasanah; Ardiansyah Japlani; Fitriani (Universitas Muhammadiyah Metro, 2026)
The aim of this research is to find out whether there is a direct and indirect influence between product quality and price on customer loyalty which is mediated by customer satisfaction with honda motorbikes. This research uses quantitative research, the population in this research is 2020 FEB management students at Muhammadiyah Metro University. Using the Slovin formula, a sample of 61 students was obtained. The data was processed using the SPSS version 26 data program. The results of this study show that product quality has a direct effect on customer loyalty on Honda motorbikes, price has a direct effect on customer loyalty on Honda motorbikes, product quality has a direct effect on customer satisfaction on Honda motorbikes, price has a direct effect on customer satisfaction on Honda motorbikes, customer satisfaction has a direct effect on customer loyalty on Honda motorbikes, product quality has an indirect effect on customer loyalty through customer satisfaction on Honda motorbikes, price has an indirect effect on customer loyalty through customer satisfaction on Honda motorbike.